2013
DOI: 10.3126/njh.v9i1.8342
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Valvular Involvement and Demographic Features of Patients on Injection Benzathine Penicillin at Dhulikhel Hospital

Abstract: Background Rheumatic heart disease (RHD) is the most common cardiovascular disease in children and young adults. Though declined and almost non-existent in developed nations, RHD is still one of the leading cause for premature death and disability in developing countries. Prevalence of RHD is high in both rural as well as urban area of Nepal. Present study is designed to look at the pattern of valvular involvement and demographic features in RHD. Methods 326 Patients indicated for inj. Benzathine penicillin we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
(1 reference statement)
3
2
0
Order By: Relevance
“…10 In our study most of the patients were taking Penicillin for RHD (88.4%) compared to for RF (11.6%) which is similar to the study done by Humagain et al 11 The penicillin injection is provided free for the patient, compliance with the treatment is good.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…10 In our study most of the patients were taking Penicillin for RHD (88.4%) compared to for RF (11.6%) which is similar to the study done by Humagain et al 11 The penicillin injection is provided free for the patient, compliance with the treatment is good.…”
Section: Discussionsupporting
confidence: 74%
“…9 ,16,18 Our study revealed that mitral valve disease was more common in female than in male whereas aortic valve disease was more common in male than female. We found AS to be more common among males like the study Humagain 11 et al however Shrestha N 17 et al found AR to be more common among males . Though adverse events in patients taking Injection Benzathine Penicillin are reported in other study, during our study period we didn't had any major adverse events.…”
Section: Discussionsupporting
confidence: 39%
“…The least common lesion is Aortic stenosis similar to other studies. We found AS to be more common in male similar to the study by Huma Jain et al [15] Aortic regurgitation is more common in female in contrary to the study by Shrestha et al [16] In our study, mitral regurgitation was the dominant valvular lesion. The cause being uncertain.…”
Section: Valvular Lesionsupporting
confidence: 85%
“…RHD is the most common finding in adolescents and young adults which is similar to the other studies from developing nations 9,10 but different from those of developed nations 1,2 . This is a known fact that RHD is common in developing countries but almost nonexistent in developed countries 5,15 . Cor-pulmonale is the most common finding in middle age group in our study.…”
Section: Discussionmentioning
confidence: 99%